Comparative Analysis of Skeletal Changes, Occlusal Changes, and Palatal Morphology in Children with Mild Class III Malocclusion Treated with Elastodontic Appliances and Bimaxillary Plates - Vincenzo Ronsivalle; Vincenzo Quinzi; Salvatore La Rosa; Rosalia Leonardi; Antonino Lo Giudice (MDPI AG, 2023)
Background: The aim of the present study was to compare the changes observed in children after the early treatment of mild class III malocclusion using bimaxillary removable plates supported by class III elastics and elastodontic devices. Methods: Twenty children (mean age 7.6 ± 1.1 years) with signs of class III malocclusion were treated using by-maxillary plates (PG group) with class III elastics (10 subjects = mean age 7.9 ± 1.3 years) or using class III elastodontic devices (EG group) (10 subjects = mean age 7.4 ± 0.8 years). Digital models and lateral cephalograms were obtained before treatment (T0) and at the end of treatment (T1). The digital models were analyzed to assess occlusal changes and maxillary morphology using the surface-to-surface matching technique. Changes in cephalometric parameters were also analyzed. The data outcomes were statistically analyzed using the paired Student's t test for inter-timing assessments and the independent Student's t test for inter-group assessments. Results: Both groups showed correction of class III malocclusions, with a significant increase in the ANB angle and the overjet (p < 0.05). Subjects in the PG group exhibited a greater reduction in the inter-incisal angle compared to the EG group (p < 0.05). The children in the EG group had a significantly lower percentage of palatal morphology matching between T0 and T1 compared to the PG group (p < 0.05), suggesting greater morphological changes in the palate. Conclusions: Elastodontic appliances (EAs) and bi-maxillary plates successfully correct class III malocclusions in children. However, elastodontic devices significantly improved the morphology of the palate, both in the transverse and anteroposterior directions.